Cutaneous Lymphoid Hyperplasia With T-Cell Clonality and Monotypic Plasma Cells Secondary to a Tick Bite: A Hidden Critter and the Power of Deeper Levels. (March 2022) - Cho, Woo Cheal; Gill, Pavandeep; Nagarajan, Priyadharsini; Aung, Phyu P.; Torres-Cabala, Carlos A.; Curry, Jonathan L.; Ivan, Doina; Lester, Laura; Prieto, Victor G.
Abstract : Abstract: Cutaneous lymphoid hyperplasia (CLH) is a benign reactive process with T-cell or B-cell lymphocytic infiltration in the skin, which can simulate cutaneous lymphomas both clinically and histologically. Various antigenic stimuli have been implicated in the development of CLH, including tick bites. Finding histologic evidence of such triggering factors, however, is often difficult. Moreover, the presence of clonality in CLH can potentially be interpreted as a neoplastic process, posing a further diagnostic challenge to dermatopathologists, if one is not aware of such peculiar phenomena. Herein, we describe a case of CLH secondary to a tick bite, featuring both T-cell clonality and monotypic plasma cells with lambda light chain restriction; the diagnostic clue being tick parts, which became evident on assessment of deeper levels. To the best of our knowledge, this is the first reported case of a tick-associated clonal CLH with simultaneous detection of monoclonal T cells and monotypic lambda light chain restriction, mimicking primary cutaneous CD4 + small/medium T-cell lymphoproliferative disorder and Borrelia -associated primary cutaneous marginal zone B-cell lymphoma, respectively.